MUMF:a mixed uni-and multicast fair scheduling scheme for CICQ switches - Hong-chao HU; Yun-fei GUO; Shu-qiao CHEN; Peng YI (Tongxin xuebao)
Based on the CICQ (combined input and cross-point buffered) switches,how to support fair scheduli for uni-and multicast traffic was discussed thoroughly.Then,comed up with an ideal theoretical switching model for CICQ switches.Based on the theoretical model,a mixed uni-and multicast fair scheduling (MUMF) scheme was proposed.With MUMF,each input port and output port can schedule variable length packets independently.Simulation results based on SPES (switch performance evaluation system) show that MUMF can provide good delay,fair and throughput performance.